The Influence of E-Service Quality, Brand Image, Security and Electronic Word Of Mouth (E-WOM) on Customer Loyalty at E-Commerce Blibli.Com in Jepara Regency - Nurul Rizka Arumsari; Muhammad Farizal Ikhsan; Dian Wismar'ein (Perspective Humanities and Social Sciences, 2025)
This study aims to analyze the influence of e-service quality, brand image, security and electronic word of mouth (E-WOM) on customer loyalty on E-Commerce Blibli.com in Jepara Regency. The research method used in this study uses quantitative research methods. The sample used in this study were E-Commerce Blibli.com customers in Jepara Regency as many as 125 respondents using purposive sampling techniques. The data collection method used a questionnaire. The data analysis method used SPSS software version 25. The results of the study showed that e-service quality had a positive and significant effect on customer loyalty, brand image had a positive and significant effect on customer loyalty, security had a positive and significant effect on customer loyalty, electronic word of mouth (E-WOM) had a positive and significant effect on customer loyalty and e-service quality , brand image , security and electronic word of mouth (E-WOM) had a positive and significant effect on customer loyalty simultaneously.